Comparing some physical abilities between indoor and outdoor football players (Texas Journal of Multidisciplinary Studies, 2024)
The research study aimed to identify the differences between some physical abilities between indoor and outdoor football players. The researcher assumed that there were significant differences in some physical abilities between indoor and outdoor football players. The researcher used the descriptive approach using the comparative survey method to suit the nature of the research, and the research community consisted of Maysan Futsal Club players, numbering (16) players.